The Analysis Of Slang Words Used In “The Boss Baby” Movie Script - Zaenal Abidin (Indonesian Journal of Multidisciplinary Science, 2021)
One of the language variations used by many people is slang. Slang is one of language variations in sociolinguistics used by society to interact each other. In this study, the author analyse the slang words used in The Boss Baby movie script. The purposes of this research are: 1) To know the types of slang words used by the characters in The Boss Baby movie; and 2) To know the reasons why the characters use some slang words in The Boss Baby movie. The author used the theory of slang words and the reasons by Eric Partirdge to answer the problem of the research. This research is descriptive qualitative and used the documentation method in collecting the data. The author discovered that there are three types of slang words used in the movie: Public house slang (kid, buddy, guys), medical slang (suck) and society slang (yeah, dad, dob, gonna, gotcha, fiflty, mommy, nada, cool, a-s-a-p, punk, bummer, gotta, wanna, guts, sweetie). Meanwhile, the reasons why the movie characters use slang words are to show or induce either friendliness, to be brief, to ease social intercouse, to sheer high spirit, to reject and to lessen the awkwardness.